Rediseño del formato impreso del diario el Universo - García Caleño, Jahaira Mercedes (2020)
We currently observe a world that requires adaptations quickly and intrepid, whether in the social or behavioral sphere, these changes include social communication; It must be at the forefront to generate transformations in the way of communicating, disseminating and reaching recipients, whether through print or digital media. Based on the premise that technological trends are here to stay and are constantly evolving, this is where the position of the print media is in danger of being relegated; since reading habits are changing not in its entirety, but in a large part. In Ecuador over the years, most of the print media have had to apply changes, among these is the newspaper El Universo, which has distinguished itself as a compact communication medium, identified with the most significant national interests and a champion in informative content; The same has been seen in the need to evolve in appearance and way of presenting the tacit news, using new drafting and layout processes, forging that the information is framed in a transcendental space for the visibility of the reader. This paper aims to carry out an analysis of the redesign of the printed format of the newspaper El Universo, as a success factor for the survival of the traditional press. Based on the above, it can be concluded that the new edition of the newspaper El Universo responds to the avant-garde changes of modern society, which is on a hurried path and its desire to stay informed provides for new modes of presentation and dissemination. It can be mentioned that this change in the conceptual image of the newspaper facilitates its foray into the new generations, be it for its print or digital edition, since, despite new reading habits imposed by technologies, there are still paper readers who enjoy managing, manipulate and immerse oneself in the experience of reading a practical, concrete, functional newspaper with reliable informative contributions.